Virologic outcomes following enhanced adherence counselling among treatment Experienced HIV positive patients at University College Hospital, Ibadan, Nigeria (2021)
Aims: To explore the impact of enhanced adherence counseling (EAC) in achieving viral suppression among our patients unsuppressed viral load in a large Anti-retroviral therapy (ART) program in South West Nigeria. Study Design: This study was a descriptive cross-sectional review of patients’ records. Place and Duration of Study: The study was conducted in human immunodeficiency virus (HIV) Program located in Infectious Disease Institute, College of Medicine, University of Ibadan, Nigeria involving review of data of patients with unsuppressed viral loads between 1st March 2017 – 30th September 2018. Methodology: We described the viral loads (VL) outcomes of patients with VLs >1 000 copies/ml after at least 6 months on ART and a comprehensive 3 monthly EAC support programme. We calculated adherence using pharmacy refill data. Patients with one VL measurement after the EAC sessions were eligible for analysis. Results: Out of 400 patients with VL >1 000 copies/ml reviewed during the study period, only 204(51.0%) were virally suppressed at the end of the 3 EAC sessions. Those with initial VLs between 1000-5000cp/ml had the highest adherence rate (73.0%) and VL suppression rate (68%). The youngest age group (16-30 years) had the least adherence (55.2%) and the least viral suppression (44.8%) while the oldest age groups (61-80years) were the most adherent (69.0%) and the most virally suppressed (55.2%). The proportion of patients on second line regimen were significantly more virally suppressed than those on the first line regimen (P <0.002). Conclusion: This study showed the role EAC in accomplishing VL suppression and the need to intensify adherence counseling at commencement of highly active anti-retroviral therapy (HAART) to strengthen adherence in people living with HIV (PLHIV) and consequently preventing raised VL at the next laboratory testing of viral load. We strongly advocate for better measurement of adherence to antiretroviral therapy that will be accessible and reliable as this was a limitation of this study.